Economic Effects of Migration from Poland to the UK - Mihaela Simionescu; Yuriy Bilan; Grzegorz Mentel (Amfiteatru Economic)
Considering that large numbers of the EU-8 immigrants was a strong argument for the Brexit, the objective of this paper is to assess some economic effects of migration from Poland to the UK for both countries. Intensive emigration of the Poles to the UK since 2004 negatively affected Poland’s economic growth in the long run, but it also reduced tensions at the labour market by decreasing the unemployment rate. On the other hand, the increase in Polish immigrants in the UK did not significantly affect economic growth and unemployment rate in the destination country in the short run in the period 2004-2015. A significance influence was observed only in the long run, when the UK economic growth decreased, but the pressures on the labour market significantly reduced. From these empirical findings, some policy recommendations are required for both countries: for Poland, migration policies to promote the return of migrants and more efficient utilization of labour force, while for the UK – shaping a more flexible labour market.